2023
DOI: 10.1101/2023.10.23.563594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A previously-unrecognized motif of transcription factor RYBP, hotspot of cancer-related mutations, is essential for the integrity ofPolycombrepressive complex 1

Catarina S. Silva,
Laura Mariño Pérez,
Irene Garcia Ferrer
et al.

Abstract: Polycomb repressive complex 1 (PRC1) catalyzes monoubiquitination of histone H2A on Lys119, promoting gene silencing. Cells at different developmental stages and in different tissues express different PRC1 isoforms. All isoforms share the same catalytic core (subunits RING1B and PCGF) and vary in the composition of regulatory subunits, clustering in two major classes. Canonical isoforms (cPRC1) are regulated by CBX-like subunits, while variant isoforms (vPRC1) are regulated by RYBP-like subunits. The molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The only ordered regions of this modeled protein are the zinc-finger domain (residues 23-47), the N-term helix (residue 59-69), and the β-hairpin motif (residue 165-175). Whereas the former and the latter are well-assessed binding spots of RYBP with some molecular partners [2], the N-term helix is a region with a high α-helical propensity predicted by AlphaFold to be fully folded and it has been recently shown that it is capable of interacting with a partner protein of RYBP, the RING1B-PCGF4 heterodimer [27]. All the other regions of the modeled RYBP are unfolded, and AlphaFold predicts that they have a low probability of adopting a structure (confidence score pLDDT < 60, where 0 is the minimum, and 100 is the maximum) [55].…”
Section: Modelling Of the Isolated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only ordered regions of this modeled protein are the zinc-finger domain (residues 23-47), the N-term helix (residue 59-69), and the β-hairpin motif (residue 165-175). Whereas the former and the latter are well-assessed binding spots of RYBP with some molecular partners [2], the N-term helix is a region with a high α-helical propensity predicted by AlphaFold to be fully folded and it has been recently shown that it is capable of interacting with a partner protein of RYBP, the RING1B-PCGF4 heterodimer [27]. All the other regions of the modeled RYBP are unfolded, and AlphaFold predicts that they have a low probability of adopting a structure (confidence score pLDDT < 60, where 0 is the minimum, and 100 is the maximum) [55].…”
Section: Modelling Of the Isolated Proteinsmentioning
confidence: 99%
“…From a structural point of view, RYBP is a 228-residue-long, highly basic intrinsically disordered protein (IDP) that binds to DNA [2,25]. As shown in Figure 1A, in the RYBP model, the primary structure includes a conserved zinc-finger motif at the N terminus, which is folded and contains the ubiquitin-binding domain [22,26] followed by a so-called 'N-term' helix [27] ending with the nuclear location signal (NLS) that allows for its nuclear translocation [28] and, further ahead, by a β-hairpin motif. The rest of the structure of the RYBP model is unfolded, including a polypeptide region rich in Lys and Arg residues and a C-terminal region with a high percentage of Ser and Thr residues.…”
Section: Introductionmentioning
confidence: 99%